Veiled power : international law and the private corporation 1886-1981 - Lustig, Doreen (Oxford : Oxford University Press, 2020)
'Veiled Power' conducts a thorough historical study of the relationship between international law and business corporations. It chronicles the emergence of the contemporary legal architecture for corporations in international law between 1886 and 1981. Doreen Lustig traces the relationship between two legal 'veils': the sovereign veil of the state and the corporate veil of the company. The interplay between these two veils constitutes the conceptual framework this book offers for the legal analysis of corporations in international law.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 10, 2020).
Keywords: Commercial law; Commercial law -- Case studies; Law; Laws of specific jurisdictions & specific areas of law